Mediation moderation Effects Of Sources Of Career Self-efficacy And Service Quality Of University On The Relationship Between Autistic Trait And Career Self-efficacy Among Malaysian Undergraduates. - Zainal, Mohd Syazwan (2024)
Autistic traits refer to specific characteristics associated with individuals on the autism spectrum and also in the general population. Examining autistic traits in the general population is crucial as it can shed light on the differences between autistic and non-autistic individuals. Moreover, understanding the distribution of autistic traits within different environments and settings can help develop targeted strategies to support individuals with specific needs related to levels of these traits. The present study aims to investigate how autistic traits impact career self-efficacy among undergraduate students in a local university in Malaysia. Additionally, the study explores whether sources of career self-efficacy and the university's service quality play a role in shaping career preparation among students. The study employed four instruments, namely Autism-Spectrum Quotient Short (AQ-Short), Career Exploration and Decision-Making Learning Experiences Scale, Higher Education PERFormanceonly (HEdPERF), and Career Decision Self-Efficacy-Short Form (CDSE-SF) to collect the data from 1344 science and social science undergraduate students in a public university in Malaysia. The undergraduate students were invited to participate in the online survey, via a stratified sampling technique. The research entailed descriptive and inferential analyses, uncovering a significant relationship between autistic traits, sources of career self-efficacy and career self-efficacy for both high and low autistic traits groups.